Larangan Hate Comment di Media Sosial Kontekstualisasi Q.S. An-Nisa’: 148 (Tinjauan Analisis Ma’na-Cum-Maghza) - Amirotussolihah Amirotussolihah; Siti Falihatul Muslihah; A. M. Ismatulloh; Ahmad Fahrur Rozi (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
The purpose of this study is to contextualize the prohibition of hate comments on social media in Q. S. An-Nisa': 148 which is related to the original meaning of jahru bi suu' minal qawl which is not only hate speech that is carried out openly, but also sirr'. This research is a type of qualitative research on the verses of the Qur'an that uses library research (Library Research) in collecting and analyzing data. The results of this study are the withdrawal of the main message indicated by Surah An-Nisa':148, namely as values or norms that can be contextualized and implemented in today's digital world communication. By using the ma'na cum maghza method, the idea of Sahiron Syamsuddin, the verse is reconstructed from the original meaning and the historical main message to further develop the main message or significance to be drawn in the present context without losing the original meaning. As for the significance of the verse, first, regarding the principle of self-control in speaking, secondly, concerning the principle of self-control in responding.